PENGENALAN NILAI MODERASI PADA ANAK USIA DINI MELALUI PERMAINAN THIS OR THAT BERBASIS APLIKASI TIKTOK - Nurhayatul Kamaliyah (Balai Diklat Keagamaan Bandung, 2021)
This research departed from the problems during the Covid-19 pandemic. Students used social media, especially TikTok as a medium of entertainment. Students have not been able to filter the content in the TikTok application, thus it is feared that it can have a negative impact on their character. The research method used was pre-experimental experiment one group pretest-posttest design. Data were analyzed using descriptive analysis, normality test, and paired sample t-test. The descriptive analysis results showed that after being given treatment, it was known that 7 students were in the high category and 14 students were in the very high category. The significance value is 0.000 0.050 or t table ≤ t count 2.093 ≤ 28.289. Hence This or That game is effective for introducing moderation values to early childhood.Keywords: Covid-19; Moderation Value; Social Media.